IMPLEMENTING HYBRID CRYPTOGRAPHY ALGORITHM TO ENHANCE THE SECURITY IN CLOUD COMPUTING - Kumar, S. Rajendira; Marimuthu, A (International Journal of Computer Sciences and Engineering, 2025)
Nowadays, both public and private sector organization have come to be increasingly dependent on Digital Statistics Processing. These Virtual data are going by means of an insecure channel from one location to any other location via networks and anyone can get that critical information without the knowledge of the sender. For protecting those crucial records, Cryptography plays a vital role in community protection. Many Cryptographic algorithms are applied by the Studies Community all around the world. Also they had some limitations and implemented for precise packages, Key size or Block size restricted to some minimum number of bits. This paper provides an implementation of Symmetric and Asymmetric Cryptography techniques and also it elaborates the Hybrid Cryptography techniques by fusing the Cryptographic algorithms. A comparison has been conducted for those Algorithms at different settings such as Sizes of data blocks, Throughput, Encryption Speed and Decryption speed. Finally, the Performance Metrics shows the better performance of the Hybrid Cryptographic Technique